15=(x+3)(x+1)

Simple and best practice solution for 15=(x+3)(x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15=(x+3)(x+1) equation:



15=(x+3)(x+1)
We move all terms to the left:
15-((x+3)(x+1))=0
We multiply parentheses ..
-((+x^2+x+3x+3))+15=0
We calculate terms in parentheses: -((+x^2+x+3x+3)), so:
(+x^2+x+3x+3)
We get rid of parentheses
x^2+x+3x+3
We add all the numbers together, and all the variables
x^2+4x+3
Back to the equation:
-(x^2+4x+3)
We get rid of parentheses
-x^2-4x-3+15=0
We add all the numbers together, and all the variables
-1x^2-4x+12=0
a = -1; b = -4; c = +12;
Δ = b2-4ac
Δ = -42-4·(-1)·12
Δ = 64
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{64}=8$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-4)-8}{2*-1}=\frac{-4}{-2} =+2 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-4)+8}{2*-1}=\frac{12}{-2} =-6 $

See similar equations:

| 10x-12+6x=-2-4x | | 7=–2s+5 | | 3x+5.4=11 | | r=15.25r-5 | | -2x-23=-11 | | (x-1)^4=48 | | 11(a)=-16 | | 5x+7+3x=6(x-2)+2x | | x4-5x^2-14=0 | | 214x+12x=4 | | -12x+14=-62 | | 5x+20=2x+55 | | 2(5-x0)-(-2)(x-3)=-(3x-4) | | 2(4–3x)–10–2x=–74 | | x-24.1=-18.4 | | 12-2x=3(3x+15 | | 56x=98 | | 12x–4=26 | | a+-45=15 | | 8x-2(x+8)=8 | | 4x+7-3x=2(x-4)+3 | | -x-9=-4 | | 1.5c-25=-23 | | 5.9x+6=3.9x+14 | | x+0.8=1 | | 4(x+2)=10(2.4+8) | | (9,-4)=(10,u) | | 103y+4y+12=180 | | 7x^2−2x^2=125 | | 2.8p=2 | | 3y+7=90 | | 5x+1=88° |

Equations solver categories